STRATEGI PENINGKATAN OPERASIONAL PANCING TONDA DI KABUPATEN ACEH BARAT - Hafinuddin Hafinuddin; Salmah Salmah; Syarifah Zuraidah; Nabila Ukhty (JURNAL PERIKANAN TROPIS, 2017)
Troll lines gear is the most dominant fishing gear at West Aceh district. It's just that the operational conditions and enhancement system of troll lines in the area is unknown, so the research of operational analysis and alternative development is very important to do. The purpose of this study is to determine the condition and alternative enhancement of troll lines for the last 5 years at PPI Aceh Barat. Methods of data collection using survey methods. The data was collected in November 2015 at PPI Aceh Barat. Data analysis for troll lines operations is using descriptive analysis and enhancement strategy is  using SWOT analysis. Troll lines operations at West Aceh District consist of praproduction, production and pascaproduction. The enhancement alternatives for troll lines operations consist of increased fisheries production at PPI Aceh Barat; optimum utilization of fish resources and sustainability of fish resources; improving facilities and infrastructure at fishing port of Aceh Barat; utilization of technology and fishing tools; stakeholder involvement to support troll lines activities Such as the supply of more complete facilities at fishing port of Aceh Barat. The result of this research shows that the troll lines is very suitable to be developed especially at PPI Aceh Barat. This can be reviewed from the financial aspect and eco-friendly troll lines